Freezing equine semen after 24 hours of cooling (Research, Society and Development, 2021)
The objective of this work is to bring about technically the equine sperm cooling and freezing method after 24 h refrigeration with four commercial diluents. The technical approach ranges from the tests that precede and prove the viability of the stallion for collection to the thawing of samples. The collection is performed by means of artificial model vagina for horses and animal dummy. After collecting and analyzing the macroscopic (color, appearance, odor and volume) and microscopic (total motility, vigor and sperm concentration) characteristics of fresh semen, seminal samples will be cooled at 5 ºC for 24 h. commercial diluents. After this period, the samples will be centrifuged and the pellet will be resuspended with commercial freezing diluent and cryopreserved at - 196 ºC in straws. The blades will be thawed at 37 ° C for use in artificial insemination.